Mapping Cultural and Social Capital in English Academic Performance: A Sociological Perspective on Indonesian Digital Natives - Nafisatul Luthfi; Rofiatun Nafiah; Andhina Ika Sunardi (Journal of Innovative and Creativity, 2026)
ABSTRACT This study maps how cultural and social capital relate to English achievement among Indonesian digital natives in higher education, conceptualizing capital not as direct skill but as a structuring sociocultural resource shaping students’ positioning within the academic field. Data were collected from 53 first-semester undergraduates at Universitas Teknologi Digital Indonesia enrolled in English 1 (Odd Semester 2025/2026). Students completed a 35-item cultural–social capital questionnaire using a six-point frequency scale, and official scores were obtained for Presentation, Writing, Skill-Based Assessment (SBA), Quiz, Midterm, and Final. Records were linked to survey responses through name harmonization (NIM for verification), after deduplication and cleaning of multi-choice cells. Analyses included reliability checks, descriptives, correlations, and domain-specific regressions. The distribution of capital indicated a shift from traditional high-brow markers toward functional literacies; institutionalized and social capital were highest. Embodied capital aligned most with SBA, and social/objectified capital aligned modestly with Quiz/Final; Writing showed near-zero associations. Multivariable models explained small variance (R²≈.05–.08), indicating that capital operated as a background structuring condition rather than a strong linear predictor of performance. Findings encourage pedagogy that integrates domestic literacy supports and students’ social lives, targeting oral confidence and writing development with context-responsive tasks, while highlighting how assessment practices may differentially recognize forms of capital within the academic field. The study links Bourdieusian capital to domain-specific English outcomes in an Indonesian HE context, demonstrating how sociocultural resources exert subtle, field-specific influence rather than large direct statistical effects. Keywords: Cultural Capital; Social Capital; English Achievement; Parental Involvement; Digital Natives; Indonesian Higher Education.